Performance of composite shear walls strengthened with FRP and subjected to blast load - Hosseini, Mahdi; Li , Haitao; Hosseini, Ahmad; Ghosh, Pritam (Revista de la Construcción. Journal of Construction, 2023)
The present paper aims to explore the performance of composite shear walls reinforced with Fiber Reinforced Polymer (FRP) sheets, subjected to blast loads. The finite-element method (FEM) implemented in the ABAQUS software is used to evaluate several numerical models to meet this objective. The parametric behavior of the system under the effect of blast load intensity was investigated, along with the FRP sheet material, concrete compressive strength, and also the geometric characteristics of wall components such as its thickness, spacing of FRP sheets, and thickness of the cross-sectional shape of the steel plates under the effect of blast load. It was found that the reinforcement of the composite shear wall by incorporating FRP sheets not only increases the stress absorption in the wall but also increases the load transfer capacity and leads to high energy dissipation using the polymer fibers. It has been found that carbon polymer sheets (CFRP) and glass polymer sheets (GFRP) have, respectively, the best and the weakest performance in shear wall stress absorption compared to AFRP sheets, and this is due to the tensile strength and low density of CFRP sheets. As the thickness of FRP sheets increases, the stress, strain and displacement created in the composite shear wall decrease, owing to the increase of the final strength, which is, in turn, the result of the increase in fiber thickness.